Cellulose and lignin are the regulators of seed hardness in guava (Psidium guajava L.) fruit: Insights for processing and fresh consumption - Shubham Jagga; Madhubala Thakre; Rakesh Bharadwaj; Poonam Maurya; Rohit Nigam; Nayan Deepak Gangappa; Arumugam Nagaraja; Manish Srivastav; Eldho Varghese; Amitha Mithra Sevanthi; Jai Chand Rana; Amritbir Riar (Applied Food Research)
Seed hardness adversely affects consumer preference and hence is an important economic trait in guava breeding (Psidium guajava L.). In this study, seed hardness was studied in 18 guava genotypes along with other related seed, fruit, and biochemical traits important for fresh consumption and processing purposes. The seed hardness ranged from 64.94 N (Hisar Surkha Variant) to 217.73 N (Sasni). It was positively and significantly correlated with the seed index (0.783), lignin content (0.719), cellulose content (0.669), seed width (0.704), fruit weight (0.696), and fruit width (0.686). In very hard seeded guava genotypes, namely Sasni and VNR Bihi, both cellulose (compactly arranged cellulose microfibrils) and lignin were deposited in the form of a thick layer. Whereas soft seeded guava genotypes Hisar Surkha Variant and Hisar Surkha, had very thin cellulose (loosely arranged cellulose microfibrils) and lignin layers. The heatmap analysis of seed hardness, cellulose content, and lignin content categorized 18 guava genotypes into very hard (Sasni, VNR Bihi, Black guava), hard (11 genotypes), and soft-seeded (Hisar Surkha Variant, Hisar Surkha, Hisar Safeda, Pant Prabhat) categories. This categorization should be taken into consideration during selection of guava variety for processing purpose as the cellulose and lignin driven seed hardness in guava can affect the product quality and its palatability.